Peripheral vascular access as exclusive access mode in pediatric intensive care unit - Armstrong, Sonya Hayes; Gangu, Shantaveer; West, Alina Nico; Spentzas, Thomas (Frontiers in Pediatrics, 2023)
Introduction The type of vascular access (central or peripheral) in pediatric critical care depends on several factors, including the duration of treatment, the properties of the medication (osmolarity or vesicant), and the need for central pressure monitoring. The utilization of peripheral intravascular catheters (PIVCs) has shown a notable increase in the number of patients being treated. Extended dwell or midline catheters are another peripheral access option in addition to PIVCs. However, there are currently no established guidelines on their placement. Objectives The aim of this study is to estimate the duration of dwell time for PIVCs, analyze the specific parameters affecting it, and develop recommendations for switching to extended dwell and midline catheter placement as an alternative to peripheral access. Methods The study enrolled patients aged 0–18 years admitted to the pediatric intensive care unit (PICU) for over 24 h and managed with peripheral access only over 2 years (2019–2021). Measurements and main results A total of 484 patients met the specified criteria. Patients who had peripheral access exhibited a lower PRISM score and a shorter length of stay in the PICU, with mean values of 18 (SD: 8.5) and 9.5 (SD: 6.4) days, respectively, compared with patients who had central access with mean values of 8.9 (SD: 5.9) and 5.7 (SD: 3.6) days, respectively. The PIVC dwell time was found to be 50.1 h (SD: 65.3) and required an average of 1.6 insertion attempts. Patients with three or more insertions exhibited an increased odds ratio of 5.2 (95% CI: 3.1–8.5) for receiving an extended dwell or midline insertion. Increased dwell time was associated with female gender, 59.5 h (P < 0.001), first attempt insertion, 53.5 h (P < 0.001), use of 24 Ga bore, 56.3 h (P = 0.04), left-sided insertions, 54.9 (P = 0.07), less agitation, 54.8 h (P = 0.02), and less edema, 61.6 (P < 0.001). Decreased dwell time was associated with the use of vancomycin infusion at 24.2 h (P < 0.001) and blood transfusions at 29.3 h (P < 0.001). Conclusions Extended catheters last longer than PIVCs in PICU patients. Extended catheter placement requires consideration of the length of treatment, as well as the overall body edema, the level of the patient's restlessness, and the need for vancomycin infusion or blood transfusions, as these factors reduce PIVC dwell time and expose the patients to painful insertions. For such cases, an extended dwell catheter may be a better option, even if the projected treatment time is less than 6 days.